KAJIAN PERBANDINGAN RESPON BANGUNAN PADA RANGKA BETON PEMIKUL MOMEN DENGAN METODE GAYA LATERAL EKIVALEN DAN RESPON SPEKTRUM - Benny Yohannes (Jurnal Teknik Sipil USU, 2014)
ABSTRACT This final project’s objective is to investigate the comparison of the response of structures in term of base shear and driftby usingstatic equivalentmethod and response spectrum methodwhich is obtained analitically SAP2000 programme version 10 at concrete structures 2D with beam and column element.The equation of equivalent lateral forces method constitutes a simple approximation contained in some building codes. There is difference between building code of Indonesia SNI 03-1726-2010 and SNI 2002 in that the former indicates equivalent static forces with the exponential factor which will be elaborated in this final project. On the other hand, the analytical solution of response spectrum method may show a discrepancy from that of empirical equation in equivalent static forces method since there have not been some variables considered in that empirical equation and this method amounts to a simple approximation.In that analysis, the writer uses some variation of 4 stories, 7 stories and 12 stories so discrepancy between response spectrum method and static equivalent method can be easily understood.The solution of this provides the elaboration of analytical results under study. The outcomes are then displayed in table together with their deviation. Keywords: Response of structure, empirical equation, response deviation of structure